Investor monitoring, money-likeness and stability of money market funds - Maija Järvenpää; Aleksi Paavola (Bank of Finland, 2021)
An asset is money-like if investors have no incentives to acquire costly private information on the underlying collateral. However, privately provided money-like assets-like prime money market fund (MMF) shares-are prone to runs if investors suddenly start to question the value of the collateral. Therefore, for risky assets, lack of money-likeness is a necessary condition for lack of run incentives. But is it a sufficient one? This paper studies the effect of the U.S. money market fund reform of 2014-2016 on investor monitoring, money-likeness and stability of institutional prime MMFs. Using the number of distinct IP addresses accessing MMFs' regulatory reports as a proxy for investor monitoring, we find that the reform increased monitoring and thus decreased money-likeness of institutional prime funds. However, we also show that after the reform, institutional prime funds that are more likely to impose the newly introduced redemption restrictions are more monitored, suggesting that investors may monitor in order to avoid being hit by the restrictions. Overall, our results indicate that increased monitoring, or decreased money-likeness, has not made institutional prime MMFs run-free, and it may have actually created a new source of fragility for MMFs.
URN:NBN:fi:bof-202102111112
Keywords: G01; G23; G28; 330; Money market funds; money markets; money market fund reform; money-likeness; information sensitivity; monitoring